After the Post-Cold War : The Future of Chinese History - Dai, Jinhua, 1959- (Book collections on Project MUSE., 2018)
In After the Post-Cold War eminent Chinese cultural critic Dai Jinhua interrogates history, memory, and the future of China as a global economic power in relation to its socialist past, profoundly shaped by the Cold War. Drawing on Marxism, post-structuralism, psychoanalysis, and feminist theory, Dai examines recent Chinese films that erase the country's socialist history to show how such erasure resignifies socialism's past as failure and thus forecloses the imagining of a future beyond that of globalized capitalism. She outlines the tension between China's embrace of the free market and a regime dependent on a socialist imprimatur. She also offers a genealogy of China's transformation from a source of revolutionary power into a fountainhead of globalized modernity. This narrative, Dai contends, leaves little hope of moving from the capitalist degradation of the present into a radical future that might offer a more socially just world.